2014
DOI: 10.1039/c3sm52285g
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, mechanical and mass transport properties of isotropic and capillary alginate gels

Abstract: Macroscopically homogeneous and inhomogeneous calcium alginate gels are formed via internal or external addition of various amounts of calcium to an alginate solution. The externally formed gels contain parallel aligned capillary structures. The mechanical and mass transport properties and the microstructure of the differently set gels were characterized by rheological measurements, fluorescence recovery after photobleaching (FRAP) and transmission electron microscopy (TEM). TEM images show a zone of distorted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 43 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…In terms of the formed matrices, a previous transmission electron microscopic study has demonstrated a nano-network architecture formed by calcium alginate similar to the fibrous structures observed in sundew adhesive [41]. However, this architecture is loosely stitched and is not as tight-knit as that obtained in sundew adhesive, comparatively [41].…”
Section: Functional Groups Aiding In the Assembly Of The Nano-networkmentioning
confidence: 95%
“…In terms of the formed matrices, a previous transmission electron microscopic study has demonstrated a nano-network architecture formed by calcium alginate similar to the fibrous structures observed in sundew adhesive [41]. However, this architecture is loosely stitched and is not as tight-knit as that obtained in sundew adhesive, comparatively [41].…”
Section: Functional Groups Aiding In the Assembly Of The Nano-networkmentioning
confidence: 95%
“…In conjunction, indirect diffusivity estimations using pore size characterization by various scanning probe microscopy (SPM) methods have been documented [14,15,16]. Other methods include spectrophotometry [17,18,19,20], size exclusion chromatography [8,21], mechanical release tests [22,23] and fluorescence microscopy [23,24,25]. Regardless of the diffusivity characterization method, the following are a sub-set of factors affecting cross-link homogeneity, size and density, gel isotropy and, thus, membrane diffusivity [13,19,20]: (1) the β- d -mannuronic (M) to α- l -guluronic (G) ratio, the distribution of each monomer within the chain, and alginate molecular weight (MW); (2) the kinetics of gelation, specifically external gelation (chelation) vs. internal gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, given that the kinetics of binding of chitosan amino groups to xanthan carboxyl groups is fast, inhomogeneous molecular distribution might be somehow expected. Different mass transport mechanisms can be observed in gels and other similar structured materials, such as hydrodynamic flow, capillary flow, and molecular self-diffusion (Hermansson 2008;Schuster et al 2014), depending on their structure. While hydrodynamic flow is observed in large and open structures, being driven by forces such as gravity and differences in chemical potential, capillary flow is noticed in gels with smaller pores and channels.…”
Section: Physico-chemical Characterization Of the Filmsmentioning
confidence: 99%